DISHARMONISASI PENGATURAN KEKAYAAN NEGARA YANG DIPISAHKAN PADA BUMN PERSERO DAN IMPLIKASINYA TERHADAP KEWENANGAN PEMERIKSAAN BPK - Muhammad Risani (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
This study aims to analyze the disharmony in the regulation of the status of separated state assets in State-Owned Enterprises in the form of Persero and its implications for the authority of the Audit Board of Indonesia (BPK). This issue arises due to the dualism of legal regimes, namely the public law regime that classifies separated state assets as part of state finances and the private law regime that regards Persero as an independent legal entity. This research employs a normative legal method using both statutory and conceptual approaches through the examination of primary and secondary legal materials, which are analyzed qualitatively. The findings reveal that the disharmony is primarily caused by normative conflicts between the State Finance Law, which adopts a public law approach, and the State-Owned Enterprises Law as well as the Limited Liability Company Law, which adopt a private law approach in determining the status of separated state assets. This condition has implications for the authority of the Audit Board of Indonesia (BPK), including ambiguity regarding the scope of audit objects, overlapping supervisory powers, and an expanded interpretation of state losses arising from the business activities of Persero companies. Therefore, an ideal legal framework is required through regulatory harmonization and a clearer delineation between public and private legal regimes in order to ensure legal certainty, effective oversight, and the protection of business management within State-Owned Enterprises in the form of Persero.